Efektivitas Kebijakan Insentif Pajak Bumi Dan Bangunan Perdesaan dan Perkotaan Pada Penerimaan Pajak Daerah Di UPPRD Senen Tahun 2022-2024 - Febi Rizkia; Alief Ramdan (Jurnal Ilmu Administrasi Publik, 2026)
Rural and Urban Land and Building Tax is one of the strategic sources of local revenue for the Provincial Government of DKI Jakarta. However, the realization of PBB-P2 revenue at UPPRD Senen during the 2022-2024 period shows fluctuations and has not fully reached the target, which is influenced by increasing taxpayer non-compliance and high arrears. To overcome this problem, the local government implemented a PBB-P2 incentive policy in the form of tax principal exemptions, principal relief, and the elimination of administrative sanctions. This study aims to analyze the effectiveness of the Rural and Urban Land and Building Tax incentive policy at the Senen UPPRD and to identify the inhibiting and driving factors that can affect local tax revenue. This study used a qualitative approach with a descriptive research type and data collection techniques through observation, interviews, and literature study. The research analysis is based on the effectiveness theory proposed by Richard M. Steers, which includes organizational factors, environmental factors, employee factors, and management factors. Based on the results obtained, it shows that the effectiveness of PBB varies each year. In 2022, the effectiveness level reached 68%, which is classified as not yet effective enough, in 2023 it was 90% and classified as quite effective, and in 2024 it was 123% and classified as very effective. The obstacle that arises is the low awareness of taxpayers, but efforts have been made by disseminating information about the PBB-P2 incentive policy evenly. Meanwhile, intensive socialization has become a driving factor in increasing PBB-P2 revenue realization and has an effect on regional revenue. Keywords: Effectiveness; PBB intensive policy; regional revenue.